B cell metabolism in autoimmune diseases: signaling pathways and interventions - Li, Jingyue; Zhao, Mingjiu; Luo, Wenjun; Huang, Jiaqi; Zhao, Bin; Zhou, Zhiguang (Frontiers in Immunology, 2023)
Autoimmune diseases are heterogeneous disorders believed to stem from the immune system’s inability to distinguish between auto- and foreign- antigens. B lymphocytes serve a crucial role in humoral immunity as they generate antibodies and present antigens. Dysregulation of B cell function induce the onset of autoimmune disorders by generating autoantibodies and pro-inflammatory cytokines, resulting in an imbalance in immune regulation. New research in immunometabolism shows that cellular metabolism plays an essential role in controlling B lymphocytes immune reactions by providing the energy and substrates for B lymphocytes activation, differentiation, and function. However, dysregulated immunometabolism lead to autoimmune diseases by disrupting self-tolerance mechanisms. This review summarizes the latest research on metabolic reprogramming of B lymphocytes in autoimmune diseases, identifying crucial pathways and regulatory factors. Moreover, we consider the potential of metabolic interventions as a promising therapeutic strategy. Understanding the metabolic mechanisms of B cells brings us closer to developing novel therapies for autoimmune disorders.